=>(12-3)*x+1=937
=>9*x=937-1
=>9*x=936
=>x=936/9
x=104
Đúng 0
Bình luận (0)
=>(12-3)*x+1=937
=>9*x=937-1
=>9*x=936
=>x=936/9
x=104
Tìm x, biết: 12x - 3x + 1 = 937. Kết quả là x =
Tìm x , biết:12x-3x+1=937 . Kết quả x là ...........................
Tìm x, biết:12x -3x+1=937. Kết quả là x=.....
Tìm x , biết: 12x - 3x + 1 = 937 . Kết quả x là
Tìm x, biết: 12x - 3x +1 = 937. Kết quả là x =
Tìm x , biết: 12x - 3x = 937 . Kết quả là x =?
Tìm , biết:12X-3X+1=937 . Kết quả là ...................
tìm x biết 12x-3x+1=937. x=?
Tìm x biết :12x -3x+1=937